Лукаш А.В., Андриенко Т.Л. Редкие и охраняемые растения Полесья (Польша, Бєларусь, Украина, Россия). – Киев: Фитосоциоцентр, 2001. – 168 с. (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Лукаш А.В., Андриенко Т.Л. Редкие и охраняемые растения Полесья (Польша, Бєларусь, Украина, Россия). – Киев: Фитосоциоцентр, 2001. – 168 с.